Menimbang Kodrat Perempuan antara Nilai Budaya dan Kategori Analisis - Kusmana Kusmana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2014)
This paper discusses the term ‘kodrat perempuan’ as a cultural value as well as a category of analysis. As a cultural value, kodrat perempuan reflects ideal measurement and standard of woman’s role. Meanwhile, as a category of analysis, it used to explain social realities where domestication and discrimination and their implications towards woman’s role can be elucidated. The source of discourse including religious discursive source plays an important role in constructing the meanings of kodrat either as a cultural value or as a category of analysis.Keywords: Nature of women, cultural values , norms, category analysis, gender, feminist.DOI: 10.15408/ref.v13i6.1000